1998
DOI: 10.1080/02841859809172196
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of invasive lobular breast carcinoma

Abstract: The sensitivity of US for lobular carcinoma was not statistically different from that of mammography. The methods were complementary, especially with regard to evaluating dense breasts and lesions which were difficult to assess clinically and mammographically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 20 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…Mann et al (17) have given this rate as 83%, and they concluded that with the use of newer, high-frequency transducers, the sensitivity of ultrasound may improve further. However, initial series using 7.5-MHz transducers showed sensitivities of 68% (15) and 78% (33), whereas series that used 10-13-MHz transducers reported sensitivities up to 98% (34,36). In our study, which used 4-9-MHz and 5-13-MHz linear array transducers, the sensitivity of ultrasonography was found to be 89.47%.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Mann et al (17) have given this rate as 83%, and they concluded that with the use of newer, high-frequency transducers, the sensitivity of ultrasound may improve further. However, initial series using 7.5-MHz transducers showed sensitivities of 68% (15) and 78% (33), whereas series that used 10-13-MHz transducers reported sensitivities up to 98% (34,36). In our study, which used 4-9-MHz and 5-13-MHz linear array transducers, the sensitivity of ultrasonography was found to be 89.47%.…”
Section: Discussionmentioning
confidence: 70%
“…The sensitivity of ultrasound is stated to range from 68% to 98% (15,(32)(33)(34)(35). Mann et al (17) have given this rate as 83%, and they concluded that with the use of newer, high-frequency transducers, the sensitivity of ultrasound may improve further.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that classic ILC is reported as normal in 40% of ultrasound cases. Other researchers reported posterior acoustic shadowing without an associated mass in 9.5%-11% of cases, 13,15 and found (2%) of cases were sonographically occult. 13 In our study, we had one case of focal shadowing without a mass (3%) and only one case was reported as normal (3%).…”
Section: Discussionmentioning
confidence: 99%
“…15 Ultrasound has an established role in determining if a clinically or mammographically apparent lesion is real or artifactual, and helps to further characterize the lesions by differentiating solid from cystic lesions. 5 It also provides guidance for interventional procedures performed in breast imaging such as biopsies, aspirations, drainages, and needle localizations.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of US for the detection of ILC has been reported to range between 25 and 88% (Paramagul et al 1995, Rissanen et al 1998. Some authors found that US significantly improves the detection of ILC in patients presenting with palpable nodules and no mammographically identified masses (Butler et al 1999, Evans & Lyons 2000.…”
Section: Ultrasoundmentioning
confidence: 99%